Zika virus displacement by a chikungunya outbreak in Recife, Brazil. - Tereza Magalhaes; Cynthia Braga; Marli T Cordeiro; Andre L S Oliveira; Priscila M S Castanha; Ana Paula R Maciel; Nathalia M L Amancio; Pollyanne N Gouveia; Valter J Peixoto-; Thaciana F L Peixoto; Helena Britto; Priscilla V Lima; et al. (Public Library of Science (PLoS), 2017)
Several arboviruses, including dengue virus (DENV), Zika virus (ZIKV) and chikungunya virus (CHIKV), transmitted by Aedes mosquitoes, circulate in northeast Brazil. Diseases caused by these viruses are of great public health relevance, however, their epidemiological features in areas where the three viruses co-circulate are scarce. Here, we present analyses of molecular and serological diagnostics in a prospective study of acute febrile patients recruited from May 2015 to May 2016 in Recife, Brazil.Two hundred sixty-three acute febrile patients with symptoms suggestive of an arboviral disease who attended an urgent heath care clinic in the Recife Metropolitan Region in northeast Brazil were enrolled. Acute and convalescent blood samples were collected and tested using molecular and serological assays for infection with DENV, ZIKV and CHIKV.Quantitative real-time reverse-transcriptase polymerase chain reactions (qRTPCR) performed on acute phase sera detected no patients positive for DENV, but 26 (9.9%) positive for ZIKV and 132 (50.2%) positive for CHIKV. There were a few suspected and only one confirmed dengue case. Specific serological assays for ZIKV and CHIKV confirmed the qRTPCR data. Analyses of DENV IgM and IgG ELISAs in the context of qRTPCR results suggested high levels of cross reactive antibodies in ZIKV-positive samples. Results from neutralization assays highly corroborated those from qRTPCR and ZIKV ELISA, indicating very few positive DENV cases. ZIKV infections were temporally clustered in the first months of the study and started to decrease concomitantly with an increase in CHIKV infections in August 2015. The proportion of CHIKV infections increased significantly in September 2015 and remained high until the end of the study period, with an average of 84.7% of recruited patients being diagnosed from August 2015 to May 2016. ZIKV infections exhibited a female bias and the cases were spread over the study site, while CHIKV cases had a male bias and were spatially clustered in each month.In 2015-2016 in the Recife Metropolitan Region, we detected the tail end of a Zika epidemic, which was displaced by a chikungunya epidemic. Few dengue cases were identified despite a high number of official dengue notifications in the area during this period. We show here important epidemiological features of these cases.